Biocompatibility and Performance of Dental Composite Restorations: A Narrative Review on Free Monomer Release, Concerns and Solutions - Aastha Dureja; Shashi Rashmi Acharya; Sandya Kini; Arun Mayya; Veena Hedge (Engineering Proceedings)
The use of resin-based dental composites is multiplying through the years due to the increased demand for tooth-colored restorations. The choice of monomers strongly determines the viscosity, reactivity, mechanical property, water sorption and polymerization shrinkage of the composite material. It is desirable for all monomers to be converted into polymers (Degree of Conversion), but this does not occur clinically, resulting in a poor prognosis for restorations as well as an increase in systemic health risks. The release of monomers occurs due to erosion and degradation, as well as the release of leachable species from the restoration. The potential toxicity of free monomers to dental pulp cells is concerning. Free monomers are not only allergens but also have reported cytotoxic and genotoxic effects. Various methods and practices have thus been employed to counter the ill effects of free monomer release from dental composite restorations for better safety and healthy oral cavities.